Biblical Apocrypha in South-Eastern Europe and Related Areas (Proceedings of the Session held at the 12th International Congress of South-East European Studies [Bucharest, 2-6 September 2019]), edited by Maria Cioata, Anissava Miltenova and Emanuela Timotin. Editura Istros, Braila (2021). Issue 1 (27th July 2022) - Condrea, Vasile
Abstract : Biblical Apocrypha in South-Eastern Europe and Related Areas (Proceedings of the Session held at the 12th International Congress of South-East European Studies [Bucharest, 2–6 September 2019]), edited by Maria Cioata, Anissava Miltenova and Emanuela Timotin. Editura Istros, Braila (2021)